Gdański Czerwiec ’76 w świetle dokumentów partii i bezpieki - Brzeziński, Piotr (Pamięć i Sprawiedliwość, 2012)
The catalyst of the June rebellion of 1976 was the dramatic rise of food prices, announced by the Prime Minister Piotr Jaroszewicz. The protest in Gdańsk differed substantially from the well-known protests in Radom, Ursus and Płock. Local workers remembered the massacre of December 1970 only too well. Fearful of provocation by the Security Service (Służba Bezpieczeństwa, SB) they chose to refrain from marching to city, beginning a sit-down strike instead; it was joined by 10,000 employees of the Lenin Shipyard, as well as a part of the personnel of ZREMB, BUDIMOR, and the Repair Plant of the Voivodeship Union of Dairy Co-operatives in Pruszcz Gdański. The Gdańsk strike was among the lar gest countrywide. Then why has the Gdańsk strike been forgotten? It’s no exaggeration to assert that in the Tri-City (Gdańsk/Sopot/Gdynia) the 1970s was a decade marked by the deep shadow of the December massacre. Very possibly the 1970 and 1980 events have erased the much less pronounced memory of the June protest. Neither did that June fi t the heroic mythology of “Polish months” of 1970 and 1980, when workers’ demands exceeded the anecdotic “sausage”. Whereas in 1976, stri king employees did not even formulate their own demands. They only protested against the rise of prices. The strike was too brief to reach beyond strictly economic issues. Therefore, there was nothing particular to be proud of years later. Neither did any spectacular government replacings occur in the aftermath of June. The disgraced Jaroszewicz remained in position of primer minister. Why? Maybe inside the Party there was no organised faction that could use the social unrest to carry out another reshuffl e among the Party’s bigwigs. Paradoxically, the image of the Coast “silent” in 1976, was permanently recorded by Andrzej Wajda’s fi lm The Man of Iron, which was inconvenient for Communist authorities. It was screened in the summer of 1981. In one of the scenes, Ms Hulewiczowa recalls that Maciej Tomczyk – the main protagonist – on becoming aware that “there have been workers’ protests in Radom and Ursus”, decided to organise a solidarity strike in the Gdańsk Shipyard: “And then something arose him. He wanted to make some protest at the shipyard, but people had too fresh memories of their own December, so they stayed idle”. That scene is very moving, but completely untrue.